Modul pedagogi PA4K: a pedagogical module of active learning for fostering 4cs skills in whole numbers and basic operations topics / Norazlin Mohd Rusdin, Siti Rahaimah Ali and Md Nasir Masran - Mohd Rusdin, Norazlin; Ali, Siti Rahaimah; Masran, Md Nasir (2020)
Modul Pedagogi PA4K was developed as a guidance for primary mathematics teachers in fostering 4Cs skills (Critical Thinking, Communication, Collaboration and Creativity) by applying active learning activities. This module apply multiple-based of active learning activities such as problem-based, projectbased, play-based, information and communication technology (ICT), singing-based as well as thinking maps which seemed to be interesting and effective in fostering 4Cs skills among pupils. The elements of the module comprising content standards, 4Cs skills and active learning activities were determined based on experts’ consensus by using Fuzzy Delphi method. 16 experts with primary mathematics and pedagogy background were involved in this study. The module was validated by 6 experts and all the items have been accepted with high percentage, above 91%. In usability study of the module where 40 of standard 3 pupils were involved, the findings of paired t-test analysis show that there were significant increasing of pupils’ 4Cs skills mastery after the module was applied in learning process. The module also achieve high average value of Cronbach’s Alpha, 0.943 in reliability test. Therefore, the module possess high quality in contents, validity and reliability values. Thus, the module may be useful for teachers and pupils in understanding and mastering 4Cs skills in 21st century education.